EFIKASI LIMBAH SAGU SEBAGAI SUBSTRAT KAYA NUTRISI UNTUK MIKROALGA ISOLAT LIPI11-2-AL002 - Dwi Susilaningsih; Sari Lestari; Kusnadi Kusnadi; Topik Hidayat; Hani Susanti (BERITA BIOLOGI, 2014)
Microalgae are photosynthetic microorganisms that have potential to produce some useful chemical substances such as carbohydrates, proteins, and lipids. Microalgae are also known exhibited ability as a bioremediation agent. This report is emphasized on analyzing the growth rate and nutritional content of microalgae including carbohydrate, protein and lipid from selected isolates LIPI11-2-AL002 that treated with sago waste. Microalgae were cultivated into hydrolysed sago “ampas” at the concentration of 0,50, 500,5000 ppm, and medium AF-6 (as control culture) respectively.Therefore selected microalgae isolate was cultivated in series of cultivation volume start from 100 mL until 5 Liter media gradually. Observed parameters were covered cell viability (growth) and proximate content of biomass including carbohydrate,lipid and protein content. The results showed that the carbohydrate and protein content in the algal biomass was increase along the addition of series sago “-ampas” concentration.The highest concentration of addition the sago ampas is 5000 ppm which is limit for the algal survival. In the highest treatment of sago waste the alga l proximate contents were 261.09 ppm of carbohydrate, 5.12 ppm of protein and 3.61% per of lipid dry weight respectively. In addition, the toxicity effect of fermentation product was not appeared in a toxicity test using gold fish komet(Carassius auratus).